Sequences and series (5)

Calculus Level 5

Let S n S_{n} , where n N n \in \mathbb N , be the sum of the infinite geometric series whose first term is n n and the common ratio is 1 n + 1 \dfrac{1}{n+1} . Find the limit below to 2 decimal places.

lim n S 1 S n + S 2 S n 1 + S 3 S n 2 + + S n S 1 S 1 2 + S 2 2 + S 3 2 + + S n 2 \large \lim_{n\rightarrow \infty} \frac{S_{1}S_{n}+ S_{2}S_{n-1} + S_{3}S_{n-2} + \cdots + S_{n}S_{1}}{S_{1}^2 + S_{2}^2 +S_{3}^2+\cdots +S_{n}^2 }


The answer is 0.5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

We note that S n = k = 0 n ( n + 1 ) k = n 1 1 n + 1 = n ( n + 1 ) n + 1 1 = n + 1 S_n = \displaystyle \sum_{k=0}^\infty \frac n{(n+1)^k} = \frac n{1-\frac 1{n+1}} = \frac {n(n+1)}{n+1-1} = n+1 . Then, we have:

L = lim n S 1 S n + S 2 S n 1 + S 3 S n 2 + + S n S 1 S 1 2 + S 2 2 + S 3 2 + + S n 2 = lim n k = 1 n S k S n k + 1 k = 1 n S k 2 = lim n k = 1 n ( k + 1 ) ( n k + 2 ) k = 1 n ( k + 1 ) 2 = lim n k = 1 n ( k + 1 ) ( n ( k + 1 ) + 3 ) k = 1 n ( k + 1 ) 2 = lim n k = 1 n ( k + 1 ) ( n + 3 ) k = 1 n ( k + 1 ) 2 k = 1 n ( k + 1 ) 2 = lim n ( n + 3 ) k = 1 n ( k + 1 ) k = 1 n ( k + 1 ) 2 1 = lim n ( n + 3 ) k = 2 n + 1 k k = 2 n + 1 k 2 1 = lim n 1 2 ( n + 3 ) ( n + 1 ) ( n + 2 ) 1 1 6 ( n + 1 ) ( n + 2 ) ( 2 n + 3 ) 1 1 = 1 2 2 6 1 = 3 2 1 = 1 2 = 0.5 \begin{aligned} L & = \lim_{n \to \infty} \frac {S_1S_n+S_2S_{n-1}+S_3S_{n-2}+ \cdots + S_nS_1}{S_1^2+S_2^2+S_3^2+ \cdots + S_n^2} \\ & = \lim_{n \to \infty} \frac {\sum_{k=1}^n S_kS_{n-k+1}}{\sum_{k=1}^n S_k^2} \\ & = \lim_{n \to \infty} \frac {\sum_{k=1}^n (k+1)(n-k+2)}{\sum_{k=1}^n (k+1)^2} \\ & = \lim_{n \to \infty} \frac {\sum_{k=1}^n (k+1)(n-(k+1)+3)}{\sum_{k=1}^n (k+1)^2} \\ & = \lim_{n \to \infty} \frac {\sum_{k=1}^n (k+1)(n+3) - \sum_{k=1}^n (k+1)^2}{\sum_{k=1}^n (k+1)^2} \\ & = \lim_{n \to \infty} \frac {(n+3)\sum_{\color{#3D99F6}k=1} ^{\color{#3D99F6}n} ({\color{#3D99F6}k+1})}{\sum_{\color{#3D99F6}k=1}^{\color{#3D99F6}n} ({\color{#3D99F6}k+1})^2} - 1 \\ & = \lim_{n \to \infty} \frac {(n+3)\sum_{\color{#D61F06}k=2} ^{\color{#D61F06}n+1} \color{#D61F06}k}{\sum_{\color{#D61F06}k=2} ^{\color{#D61F06}n+1} {\color{#D61F06}k}^2} - 1 \\ & = \lim_{n \to \infty} \frac {\frac 12 (n+3)(n+1)(n+2)-1}{\frac 16 (n+1)(n+2)(2n+3)-1} - 1 \\ & = \frac {\frac 12}{\frac 26} - 1 = \frac 32 - 1 = \frac 12 = \boxed{0.5} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...